Asthma phenotypes and IgE responses. Issue 1 (January 2016) - Froidure, Antoine; Mouthuy, Jonathan; Durham, Stephen R.; Chanez, Pascal; Sibille, Yves; Pilette, Charles
The discovery of IgE represented a major breakthrough in allergy and asthma research, whereas the clinical interest given to IgE in asthma has been blurred until the arrival of anti-IgE biotherapy. Novel facets of the complex link between IgE and asthma have been highlighted by the effect of this treatment and by basic research. In parallel, asthma phenotyping recently evolved to the concept of endotypes, relying on identified/suspected pathobiological mechanisms to phenotype patients, but has not yet clearly positioned IgE among biomarkers of asthma. In this review, we first summarise recent knowledge about the regulation of IgE production and its main receptor, FcεRI. In addition to allergens acting as classical IgE inducers, viral infections as well as air pollution may trigger the IgE pathway, notably resetting the threshold of IgE sensitivity by regulating FcεRI expression. We then analyse the place of IgE in different asthma endo/phenotypes and discuss the potential interest of IgE among biomarkers in asthma. We summarise regulation of IgE production, and discuss IgE in different asthma endo/phenotypes and among biomarkers http://ow.ly/TLxcW